Analisis Kekuatan Tarik Sambungan Plat Stainless Steel 316L pada Proses Spot Welding - Prakoso, Adjie Caesar; Lubis , Sobron Yamin; Rosehan, Rosehan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This study aims to determine the effect of variations in welding current and distance on the strength of the weld on 316L stainless steel material through a tensile test. The type of research method and data collection will begin through the welding process of eighteen pairs of stainless steel plates using spot welding. Welding will be carried out with variations in the current and distance of the welding points. After carrying out the stainless steel welding process, a tensile test will then be carried out to determine the effect of current variations and the distance of the welding points on the strength of the welded joints in stainless steel. Based on the results of the test data obtained, it shows that a voltage of 1.75 V produces an electric power of 6317.88 Watts and a voltage of 2.20 V produces an electric power of 9249.93 Watts with a constant welding time of 2 seconds. The highest tensile strength is specimen D with a spacing of 10 mm and a voltage of 2.20 V, which is 14,765 N, while the lowest tensile strength is specimen C with a spacing of 30 mm and a voltage of 1.75 V, which is 10,224 N. At a current voltage of 1.75 Volts, the welding distance is 20 mm produced is 3490.17 Mpa and a current voltage of 2.20 Volts 20 mm welding distance produced is 3682.33 Mpa the results obtained the greater the current used, the greater the resulting tensile strength. The value of the elastic modulus is inversely proportional to the current strength and welding distance. This can be shown in the results of the tensile strength test data obtained, namely specimens with a current of 1.75 volts with a welding distance of 10 mm have a greater modulus value than specimens with a current of 2.20 volts with a welding distance of 10 mm.